Development of Alectinib-Suspended SNEDDS for Enhanced Solubility and Dissolution - Eun Ji Park; Seung Ah Choi; Kyoung Ah Min; Jun-Pil Jee; Sung Giu Jin; Kwan Hyung Cho (MDPI AG, 2022)
Alectinib hydrochloride (ALH), a tyrosine kinase inhibitor, is a practically water-insoluble drug classified as BCS class IV. The present study aimed to develop novel suspended self-nanoemulsifying drug delivery system (Su-SNEDDS) to enhance the solubility and dissolution rate. The Su-SNEDDS was prepared by saturation and suspension of ALH in SNEDDS with ultrasonication energy. According to evaluation by the dispersion test and the results of particle size analysis, the selected SNEDDS composed of Kolliphor HS 15 and Capmul MCM C8 as surfactant and oil, respectively, showed a complete dissolution within 30 min. However, the SNEDDS loaded and solubilized only small amount of ALH (<0.6%, w/w). On the other hand, 10% ALH-loaded Su-SNEDDS containing small and micronized ALH particles of <5 μm had about 20-fold higher ALH-loading% than the SNEDDS and reached a 100% dissolution rate within 30 min in 1% sodium lauryl sulfate (SLS) pH 1.2 buffer. In the dispersion test and microscopic observation, micronized ALH particles in the Su-SNEDDS were readily dispersed in the dissolution medium with spontaneous nanoemulsion formation and instantly solubilized with the aid of SLS. Taken together, our results suggest that the Su-SNEDDS would be a potent oral dosage form to enhance the solubilization and dissolution rate of ALH in a new technological way.